2013
DOI: 10.1080/07409710.2013.849997
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Desperation: Motivations for Dumpster™ Diving for Food in Vancouver

Abstract: In the global food system, food is considered a disposable commodity and waste is produced at extraordinarily high levels. In a number of affluent nations, including Canada, "dumpster diving" for food has emerged as an approach to food provisioning. This article is based on a research project conducted for an honors thesis that examines dumpster diving for food in Vancouver, British Columbia. While an earlier report (Miewald 2009) identified dumpster diving in Vancouver as a survival strategy for people living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…These emerging initiatives are now attracting the attention of researchers. These include such features as farmers' markets, community gardens (Beilin & Hunter 2011) and local food swaps, which tend to be informal and often held at public spaces like a reserve, school yard or neighbourhood house, as well as the more radical actions such as gleaning and 'urban foraging' (Carolsfeld & Erikson 2013;Edwards & Mercer 2013).…”
Section: The Global Food System and Localised Responsesmentioning
confidence: 99%
“…These emerging initiatives are now attracting the attention of researchers. These include such features as farmers' markets, community gardens (Beilin & Hunter 2011) and local food swaps, which tend to be informal and often held at public spaces like a reserve, school yard or neighbourhood house, as well as the more radical actions such as gleaning and 'urban foraging' (Carolsfeld & Erikson 2013;Edwards & Mercer 2013).…”
Section: The Global Food System and Localised Responsesmentioning
confidence: 99%
“…At the other end of the spectrum are grassroots approaches in which city residents self-organize to create individual or collective gardens by investing labor in vacant public or private spaces over which access rights are nebulous and without legal authority (Carpenter 2009;Adams, Hardman, and Larkham 2015). Related literature identifies social negotiations (with restaurant owners and diners, begging) (Downey 2016), and scavenging in dumpsters for food considered "waste" (Carolsfeld and Erikson 2013) as additional mechanisms of resource access in cities.…”
Section: Access To Natural Resources In Urban Environmentsmentioning
confidence: 99%
“…Research on the topic has proliferated since Ferrell's book. For example, studies have shown that voluntary dumpster divers are mostly middle class and well educated (Carolsfeld and Erikson 2013;Edwards and Mercer 2007;Vinegar, Parker, and McCourt 2016) and that they are not simply outside consumer society but play with notions of value at its margins (Brosius, Fernandez, and Cherrier 2012;Clark 2004;Fernandez, Brittain, and Bennett 2011;Giles 2014;Gross 2009; Guillard and Roux 2014; Lehtonen and Pyyhtinen 2020).…”
Section: Pragmatic Sociology Of Critique: What Is At Stake In Dumpstementioning
confidence: 99%